Non-variceal Upper Gastrointestinal Bleeding and Its Endoscopic Management - Wasserman, Reid D.; Abel, William; Monkemuller, Klaus; Yeaton, Paul; Kesar, Vivek; Kesar, Varun (Turkish Journal of Gastroenterology, 2024)
Upper gastrointestinal bleeding (UGIB) is a major cause of morbidity and mortality. Clinical symptoms that patients may present with include: hematemesis, coffee-ground emesis, melena, and hematochezia. Clinical signs can range from tachycardia to shock. The anatomical landmark that differentiates upper gastrointestinal (GI) bleeds from lower bleeds is the ligament of Treitz. The first steps of treating a patient who presents with signs of UGIB are resuscitation with appropriate fluids and blood products as necessary. The consideration of endoscopy and the urgency at which it should be performed is also vital during initial resuscitation. Endoscopic therapy should ideally be performed within 24 hours of presentation after initial stabilization with crystalloids and blood products. Intravenous proton pump inhibitors are the mainstay in the initial management of upper GI bleeding from a non-variceal etiology, and they should be administered in the acute setting to decrease the probability of high-risk stigmata seen during endoscopy. Pro-kinetic agents can be given 30 minutes to an hour before endoscopy and may aid in the diagnosis of UGIB. There are 3 broad categories of endoscopic management for UGIB: injection, thermal, and mechanical. Each endoscopic method can be used alone or in combination with others; however, the injection technique with epinephrine should always be used in conjunction with another method to increase the success of achieving hemostasis. In this review article, we will review the steps of triage and initial resuscitation in UGIB, causes of UGIB and their respective management, several endoscopic techniques and their effectiveness, and prognosis with a primary focus limited to non-variceal bleeding Cite this article as: Wasserman RD, Abel W, Monkemuller K, Yeaton P, Kesar V, Kesar V. Non-variceal upper gastrointestinal bleeding and its endoscopic management. Turk J Gastroenterol. 2024;35(8):599-608.